The Influence of Green Entrepreneurship Orientation, Green Market Orientation, and Organizational Support on the Adoption of Green Innovations - Anjelina Sirin; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
Environmental sustainability has become a critical concern for MSMEs, particularly in the natural dye batik industry in the Special Region of Yogyakarta. This study aims to examine the influence of green entrepreneurial orientation, green market orientation, and organizational support on the adoption of green innovations. A total of 100 MSME owners were surveyed using a non-probability sampling method through structured questionnaires. Instrument testing confirmed that all items were valid and reliable, while classical assumption tests indicated normally distributed data and a regression model free from multicollinearity and heteroscedasticity. The results reveal that green entrepreneurial orientation, green market orientation, and organizational support each have a significant positive effect on the adoption of green innovations. These findings suggest that fostering environmentally oriented entrepreneurial and market practices, supported by organizational backing, can enhance the adoption of sustainable innovations among batik MSMEs. This study contributes to both theory and practice by highlighting the key organizational and market factors that promote green innovation adoption in traditional craft industries.